1982
DOI: 10.1093/nar/10.8.2709
|View full text |Cite
|
Sign up to set email alerts
|

Amount and distribution of 5-methylcytosine in human DNA from different types of tissues or cells

Abstract: Analysis of the total base composition of DNA from seven different normal human tissues and eight different types of homogeneous human cell populations revealed considerable tissue-specific and cell-specific differences in the extent of methylation of cytosine residues. The two most highly methylated DNAs were from thymus and brain with 1.00 and 0.98 mole percent 5-methylcytosine (m5C), respectively. The two least methylated DNAs from in vivo sources were placental DNA and sperm DNA, which had 0.76 and 0.84 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
554
3
13

Year Published

1984
1984
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 918 publications
(605 citation statements)
references
References 41 publications
35
554
3
13
Order By: Relevance
“…Because approximately 70% of cytosine residues at CpG dinucleotides are methylated, these findings are consistent with deamination of 5-methylcytosine and subsequent conversion to a thymine after enzymatic replication. 27 These findings support previous work demonstrating that formalin fixation increases the rate of deamination 28 and suggests that methylated cytosines are especially susceptible to this effect. Despite these differences, examination of the total base changes revealed that all types of high-quality discrepancies were rare and, as described above, did not affect the ability to make high-quality consensus variant calls.…”
Section: Evaluation Of Formalin Fixationeinduced Sequencing Artifactssupporting
confidence: 88%
“…Because approximately 70% of cytosine residues at CpG dinucleotides are methylated, these findings are consistent with deamination of 5-methylcytosine and subsequent conversion to a thymine after enzymatic replication. 27 These findings support previous work demonstrating that formalin fixation increases the rate of deamination 28 and suggests that methylated cytosines are especially susceptible to this effect. Despite these differences, examination of the total base changes revealed that all types of high-quality discrepancies were rare and, as described above, did not affect the ability to make high-quality consensus variant calls.…”
Section: Evaluation Of Formalin Fixationeinduced Sequencing Artifactssupporting
confidence: 88%
“…Human DNA was purified and M. luteus DNA (Sigma) was repurified as described previously (18). They were enriched in m5C in a mostly strandasymmetrical fashion by nick translation after pre-nicking as above except that m5dCTP (P-L Biochemicals), dGTP, dTTP, and dATP were the triphosphates used and the DNase digestion was for 10 min to give "'4-20 kb length products.…”
Section: Methodsmentioning
confidence: 99%
“…The normally programmed occurrence of de novo methylation is also evidenced by the considerably lower methylation level of the highly repeated sequence fraction of human sperm DNA than that of somatic tissue DNAs (18).…”
Section: Introductionmentioning
confidence: 99%
“…Between 60% and 90% of all CpGs are methylated in mammals [Ehrlich et al, 1982]. Methylation near gene promoters (with or without a CpG island) varies considerably depending on cell type, with higher promoter methylation correlating with low or no transcription [Suzuki and Bird, 2008].…”
Section: Dna Methylation and Demethylationmentioning
confidence: 99%